THE ROLE OF PRINCIPLES OF LEGALITY AND THE RULE OF LAW IN ENSURING PRE-TRIAL INVESTIGATION AND THE RIGHTS OF ITS PARTICIPANTS - Danshyn, M. V.; Kolesnyk, H. R. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2017)
the article reveals the role of the principles of legality and the rule of law in providing pre-trial investigation of criminal offenses and the rights of its participants, and also substantiates the need to deepen scientific research on this topical issue.